Biological control strategies for Fusarium wilt to enhance production efficiency and quality of 'Ambon' banana seedlings - Febry Nurhidayati; Didik Suryadi; Dewi Nawang Suprihatin (Faculty of Agriculture, Universitas Malikussaleh, 2026)
Fusarium wilt disease is a serious threat to the banana agribusiness system, significantly reducing production efficiency starting from the nursery phase. This study aimed to evaluate the efficacy of biological control agents (Streptomyces and Bacillus) in suppressing the progression of the pathogen Fusarium oxysporum f. sp. cubense (Foc) and enhancing the growth of 'Ambon' banana seedlings through in planta assays. The experiment employed a completely randomized design with nine combinations of isolates. The results demonstrated that the application of bio-agents significantly reduced disease progression and improved the physiological quality of the seedlings. The consortium of Streptomyces S01 and Bacillus B16 exhibited the highest biocontrol efficacy, recording a disease intensity of 38.88% and the lowest area under disease progress curve value. Meanwhile, the combination of Streptomyces S01 and Bacillus B01 produced the optimal plant height of 60.22 cm. Notably, the endophytic isolate Bacillus B16, applied individually, maintained root weight comparable to healthy, uninfected seedlings. Economically, integrating these antagonistic microbes offers a more efficient and sustainable nursery system by reducing reliance on chemical inputs.